Review of investigation the parasitic fauna of deer (fam. Cervidae/ subfam. Cervinae) in southeast Europe (VETERINARIA, 2020)
Overview of the deer (Fam. Cervidae/Subfam. Cervinae) parasitofauna in Southeastern Europe. Health control represents an inseparable segment of the wildlife menagement whether in free roaming or farming population. Having knowledge on the wildlife health status enables health preservation of the wildlife, but also of human and domestic animal health considering the wild animals as potential reservoars to infective disesases. The parasitofauna status of the game is a valuable segment of the total epizootic situtation in order to implement the game health control programs. This paper presents the most important available data on the deer parasitofauna (Fam. Cervida/subfam. Cervinae) in Southeastern Europe.
Keywords: parasitic fauna; deer; Southeastern Europe